The Role of Bhabinkamtibmas Through Counseling for the Prevention of Narcotics Abuse in the Jurisdiction of Brebes Police Station (Indonesian Journal of Police Studies, 2024)
Narcotics abuse is one of the largest and most prominent cases in Brebes Regency. The strategic location of Brebes Regency through the Pantura route makes Brebes the key to the crossing of trade in Java, including narcotics. The National Police of the Republic of Indonesia through the Bhabinkamtibmas Polres Brebes has carried out counseling on narcotics to the public in the jurisdiction of the Brebes Police Station. However, its implementation is considered still lacking which is marked by the increase in cases of narcotics abuse every year. This final project aims to describe the role of Bhabinkamtibmas counseling in preventing Narcotics abuse in the jurisdiction of Brebes Police Station, as well as find efforts to make Bhabinkamtibmas counseling better. To analyze extension activities, POAC management theory, 6M theory, and SWOT analysis theory are used. The concepts used are the concept of counseling, the concept of Bhabinkamtibmas, and the concept of Narcotics abuse. The approach taken is a qualitative approach with a type of analytical descriptiveresearch. Data collection methods include interviews, observations, document review, as well as validity and reliability by combining theory with existing concepts, data sources, and data collection techniques. The results of the study found that the implementation of counseling by the Bhabinkamtibmas jurisdiction of Brebes Police Station still has some shortcomings when related to theories and observations in the field. Therefore, the author advises the Brebes Police Bhabinkamtibmas Unit to issue duty warrants to members of other functions in becoming temporary acting officers and cooperate with the National Narcotics Agency to improve the quality of personnel and counseling materials on narcotics.
Keywords: Penyuluhan, Bhabinkamtibmas, Penyalahgunaan Narkotika